The Influence of Work Motivation and Work Discipline on Employee Performance: Study at an Automotive Company in Bandung - Nuryuliadin, Mochamad Rizki; Hadian, Dedi; Yusup, Maulana; Nurhadian, Adhie Fasha; Coenraad, Dhea Perdana; Sholihah, Sana (P3M, STIE Pasundan, Bandung, Indonesia., 2024)
This study seeks to examine the impact of Work Motivation and Work Discipline on Employee Performance at an automobile firm in Bandung. Work motivation and work discipline are essential determinants of organizational performance. The employed research strategy is quantitative, utilizing a route analysis methodology to elucidate the relationship among these factors. Data was gathered via surveys completed by employees at the branch. The study's results demonstrate that Work Motivation significantly influences Employee Performance. Employees with elevated job motivation typically exhibit superior performance, evidenced by enhanced productivity and quality of their output. Furthermore, Work Discipline has been demonstrated to influence Employee Performance positively. Disciplined personnel exhibit greater adherence to company regulations and protocols, hence facilitating the attainment of organizational objectives. This study finds that integrating elevated work motivation and strong work discipline markedly enhances employee performance at an automobile firm in Bandung. These findings underscore the need for management to formulate effective measures to enhance motivation and work discipline to attain optimal employee performance. Consequently, organizations should prioritize personnel development programs that enhance both dimensions to facilitate the attainment of corporate objectives.